2012
DOI: 10.5694/mja11.11505
|View full text |Cite
|
Sign up to set email alerts
|

Case series of four patients with strongyloides after occupational exposure

Abstract: Case series of four patients with strongyloides after occupational exposure TO THE EDITOR: Strongyloidosis in Australia has been reported in Indigenous Australians, war veterans who have served in SouthEast Asia and travellers and immigrants from regions in which strongyloidosis is endemic. 1,2 The condition is caused by Strongyloides stercoralis, and chronic infection with the nematode is maintained by an autoinfective life cycle. The consequences of infection range from asymptomatic minor infection to chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Though limited to case reports, this study identified only one case of hyperinfection and no cases of dissemination or death due to Strongyloides with the use of low‐dose MTX monotherapy. Of the subjects exposed to low doses of MTX, only three cases were not exposed to corticosteroids, of these one had hyperinfection and none had dissemination or died . Eosinophilia is known to be a poor diagnostic tool for identifying dissemination or hyperinfection ; this was confirmed in this report.…”
Section: Discussionsupporting
confidence: 74%
“…Though limited to case reports, this study identified only one case of hyperinfection and no cases of dissemination or death due to Strongyloides with the use of low‐dose MTX monotherapy. Of the subjects exposed to low doses of MTX, only three cases were not exposed to corticosteroids, of these one had hyperinfection and none had dissemination or died . Eosinophilia is known to be a poor diagnostic tool for identifying dissemination or hyperinfection ; this was confirmed in this report.…”
Section: Discussionsupporting
confidence: 74%
“…Australia's Indigenous communities have high prevalence of strongyloidiasis (disease resulting from S. stercoralis ) as do immigrants from other endemic countries, travellers to these countries and military personnel who have spent time in endemic regions [6], [7]. Soulsby, Hewagama and Brady [8] report four cases of strongyloidiasis in non-Indigenous people resulting from work-related exposure presenting at Alice Springs Hospital and by implication acquired indirectly from Indigenous populations. Those infected included a teacher at an Indigenous school, a child care worker, an ex-nurse and a paediatrician.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperinfection by Strongyloides stercoralis is mainly seen amongst immunocompromised individuals with a high case fatality rate of around 60%. (19)(20)(21) The mortality rate of the patients having hyperinfection of the present study was 33.3%. This is characterized by an acceleration of the normal life cycle of Strongyloides stercoralis that increases its burden either in the skin or lungs or gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 82%